2012
DOI: 10.1371/journal.pone.0042713
|View full text |Cite
|
Sign up to set email alerts
|

Timed Maternal Melatonin Treatment Reverses Circadian Disruption of the Fetal Adrenal Clock Imposed by Exposure to Constant Light

Abstract: Surprisingly, in our modern 24/7 society, there is scant information on the impact of developmental chronodisruption like the one experienced by shift worker pregnant women on fetal and postnatal physiology. There are important differences between the maternal and fetal circadian systems; for instance, the suprachiasmatic nucleus is the master clock in the mother but not in the fetus. Despite this, several tissues/organs display circadian oscillations in the fetus. Our hypothesis is that the maternal plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
111
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 55 publications
9
111
1
2
Order By: Relevance
“…The effects of altered photoperiod during pregnancy on fetal development and postnatal physiology are just beginning to be explored (15,32,44,48,49). Here we show that, under constant gestational light conditions, as many as 3,431 transcripts displayed changes in their expression level in the fetal liver.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…The effects of altered photoperiod during pregnancy on fetal development and postnatal physiology are just beginning to be explored (15,32,44,48,49). Here we show that, under constant gestational light conditions, as many as 3,431 transcripts displayed changes in their expression level in the fetal liver.…”
Section: Discussionmentioning
confidence: 67%
“…We have recently reported that exposure of pregnant rats to constant light from midgestation induces intrauterine growth retardation and marked effects on both fetal adrenal physiology and cardiac transcriptome (15,32). Moreover, in the adult offspring that had been gestated under constant light, we also found increased basal plasma glucose and glucose intolerance (49).…”
mentioning
confidence: 60%
See 3 more Smart Citations